GSTO1‐1 is an upstream suppressor of M2 macrophage skewing and HIF‐1α‐induced eosinophilic airway inflammation. Issue 5 (2nd March 2020) - Sokulsky, Leon A.; Goggins, Bridie; Sherwin, Simonne; Eyers, Fiona; Kaiko, Gerard E.; Board, Philip G.; Keely, Simon; Yang, Ming; Foster, Paul S.
Abstract: Background: Glutathione S‐transferases omega class 1 (GSTO1‐1) is a unique member of the GST family regulating cellular redox metabolism and innate immunity through the promotion of LPS/TLR4/NLRP3 signalling in macrophages. House dust mite (HDM) triggers asthma by promoting type 2 responses and allergic inflammation via the TLR4 pathway. Although linked to asthma, the role of GSTO1‐1 in facilitating type 2 responses and/or HDM‐driven allergic inflammation is unknown. Objective: To determine the role of GSTO1‐1 in regulating HDM‐induced allergic inflammation in a preclinical model of asthma. Methods: Wild‐type and GSTO1‐1‐deficient mice were sensitized and aeroallergen challenged with HDM to induce allergic inflammation and subsequently hallmark pathophysiological features characterized. Results: By contrast to HDM‐challenged WT mice, exposed GSTO1‐1‐deficient mice had increased numbers of eosinophils and macrophages and elevated levels of eotaxin‐1 and ‐2 in their lungs. M1 macrophage‐associated factors, such as IL‐1β and IL‐6, were decreased in GSTO1‐1‐deficient mice. Conversely, M2 macrophage factors such as Arg‐1 and Ym1 were up‐regulated. HIF‐1α expression was found to be higher in the absence of GSTO1‐1 and correlated with the up‐regulation of M2 macrophage markers. Furthermore, HIF‐1α was shown to bind and activate the eotaxin‐2 promotor. Hypoxic conditions induced significant increases in the levels of eotaxin‐1 and ‐2 in GSTO1‐deficient BMDMs, providing a potential link between inflammation‐induced hypoxia and the regulation of M2 responses in the lung. Collectively, our results suggest that GSTO1‐1 deficiency promotes M2‐type responses and increased levels of nuclear HIF‐1α, which regulates eotaxin (s)‐induced eosinophilia and increased disease severity. Conclusion & Clinical Implication: We propose that GSTO1‐1 is a novel negative regulator of TLR4‐regulated M2 responses acting as an anti‐inflammatory pathway. The discovery of a novel HIF‐1α‐induced eotaxin pathway identifies an unknown connection between hypoxia and the regulation of the severity of allergic inflammation in asthma.